Pengaruh Kekurangan Protein Pre dan Postnatal Terhadap Mineralisasi Gigi - Pinandi Sri Pudyani (Faculty of Dentistry, Universitas Indonesia, 2015)
The accuracy of nutrition quantity during and after pregnancy is needed for supporting division, differentiation and replication of cells during growth stage. Protein is needed to obtain optimally child's body growth and development including tooth. The study was aimed to deteremine the effects of pre and postnatal protein deficiency on tooth mineralization rats model. The study was carried out on 30 Rates norvegicus rats, divided in 3 groups.The first group was fed the protein deficient diet (4%) during pre and postnatal period, the second was fed the protein deficient diet (4%) only postnatal and the third was fed the postnatal diet. Feeding was carried out until animales aged at 56 days. After that, animals were sacrificed and the width of right mandibular molar prevention layer was histologically analyzed to know the number of tooth mineralization. The result of the study showed significant differences (p<0.05) in width of prevention layer between standard and experimental groups. It's concluded that pre and postnatal protein deficiency were inhibits tooth mineralization.